CYSTS INFECTIVITY OF SARCOCYSTIS SP. IN ALPACAS (VICUGNA PACOS) IN A LIVESTOCK OF THE CENTRAL HIGHLANDS OF PERU - Leguía, Guillermo (2019)
A prospective longitudinal study was performed to determine the infectivity of Sarcocystis sp. cysts in alpacas in a livestock of the central highlands in Peru. Fifty raised male alpacas were selected at random after birth and then slaughtered, 3 monthly until one year of age, in order to detect micro or macrocysts in the skeletal and cardiac muscles. Dog groups free of parasites were infected monthly with skeletal and cardiac muscle to investigate their infectivity. The results show that the raised alpacas presented micro cysts of Sarcocystis sp. in skeletal and cardiac muscle since four months of age. We did not detect macro cysts in the skeletal muscles in the raised alpacas until the end of the experiment. Dogs feed monthly on microcysts of Sarcocystis sp since birth until a year of age but does not eliminate micro or macrocyst of Sarcocystis sp.